PENGARUH FAKTOR MAKROEKONOMI DAN FAKTOR SPESIFIK BANK TERHADAP NON PERFORMING LOAN PADA PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Desy Pratifa; Syarifah Rahmawati (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2019)
Abstract:This study aims to examine the effect of macroeconomic factor and bank specific factor to non performing loan in banking companies that listed in Indonesia Stock Exchange (IDX). The macroeconomic factor that seen from inflation and bank specific factors are represented by indicators of operational expense to operating income (BOPO), bank size (size), Capital Adequacy Ratio (CAR), Return on Equity (ROE) and Loan to Deposit Ratio (LDR).This study uses panel data of 35 banking companies in Indonesia during the period of 2013 until 2016 and were analyzed using the estimation method, Ordinary Least Square (OLS).The results showed that : (1) Inflation has negative effect and significant to NPL; (2) BOPO has positive effect and significant to NPL; (3) Size has positive effect and significant to NPL; (4) CAR has negative effect but not significant to NPL; (5) ROE has negative effect and significant to NPL; (6) LDR has positive effect and significant to NPL in banking industry of Indonesia.Keywords: Inflation, BOPO, size, CAR, ROE, LDR and NPL.